Comparison of pork carcass evaluation procedures - Stiffler, D.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Carcass data were obtained from 28 barrows from the Kansas Swine Testing Station and 31 from the Kansas State Barrow Contest in 1969. All were slaughtered and standard measurements taken. Each carcass was cut to wholesale cuts by the conventional K.S.U. lab method. Cut-out data were used to calculate ham-loin index, four lean-cut percentages (live and carcass weight), percent ham plus loin of live and carcass weight, and dollar value of five wholesale cuts per hundred weight of carcass.
Swine Industry Day 1970 is known as Swine Day, 1970
Keywords: Swine; Pork carcass; Price of cuts